THE CONSTRUCTION OF MENS REA AND THE CRIMINALIZATION OF DISCRETION IN INDONESIA - Pardomuan Robinson Sihombing (LPPM Universitas Muria Kudus, 2026)
Law enforcement of corruption crimes in Indonesia faces a fundamental paradox between the demands of integrity and the need for public officials' discretionary flexibility. The phenomenon of